Screening of patients with juvenile idiopathic arthritis and those with rheumatoid arthritis for celiac disease in southwestern Iran - Moghtaderi, Mozhgan; Farjadian, Shirin; Aflaki, Elham; Honar, Naser; Alyasin, Soheila; Babaei, Maryam (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Celiac disease (CD) is a common enteropathy triggered by the ingestion of gluten in genetically susceptible individuals. It is frequently found in conjunction with other autoimmune diseases. The purpose of this study was to investigate the prevalence of CD in patients with juvenile idiopathic arthritis (JIA) and those with rheumatoid arthritis (RA) in southwestern Iran. Materials and Methods: A total of 53 children with JIA and 55 adults with RA were enrolled. Anti-tissue transglutaminase (tTG) immunoglobulin (Ig) A serum levels were measured by performing an enzyme-linked immunosorbent assay. Patients with anti-tTG IgA serum levels of >15 U/mL were considered seropositive and subjected to upper gastrointestinal endoscopy. Duodenal biopsies were histopathologically evaluated based on the modified Marsh classification. Results: One child with JIA (1.8%) and six adults with RA (11.3%) were positive for the anti-tTG IgA antibody, but the histopathological evaluations of the duodenal biopsies in these patients revealed no evidence of CD-related enteropathy. Conclusion: Although the investigation of anti-tTG antibodies is widely used as a noninvasive serologic test for the initial diagnosis of CD, because of the high positive predictive value, the clinical utility of this test alone for making a diagnosis is doubtful. We found no cases of CD among our patients with JIA and RA. The periodic screening of rheumatologic patients with positive anti-tTG IgA for CD can be helpful in making an early diagnosis of CD in these patients.